Direct control of active and reactive power for a grid-connected single-phase photovoltaic inverter - Eyad Radwan; Mutasim Nour; Ali Baniyounes; Khalid S. Al Olimat; Emad Awada (Institute of Advanced Engineering and Science, 2021)
This paper presents a single-phase grid-connected photovoltaic system with direct control of active and reactive power through a power management system of a Photovoltaic inverter. The proposed control algorithm is designed to allow maximum utilization of the inverter’s available KVA capacity while maintaining grid power factor and current total harmonic distortion (THD) requirements within the grid standards. To reduce the complexity and improve the efficiency of the system, two independent PI controllers are implemented to control single-phase unipolar PWM voltage source inverter. One controller is used to control the power angle, and hence the active power flow, while the other controller is used to control the reactive power, and consequently the power factor by adjusting the voltage modulation index of the inverter. The proposed system is modelled and simulated using MATLAB/Simulink. The PV inverter has been examined while being simultaneously connected to grid and local load. Results obtained showed the ability of the PV inverter to manage the active and reactive power flow at, and below rated levels of solar irradiances; resulting in an increased inverter utilization factor, and enhanced power quality. The proposed system, was capable of operating at power factors in the range of 0.9 lead or lag for reactive power compensation purposes and delivered its power at a wide range of solar irradiance variations.